Burden of cancers associated with the human papilloma virus in Latin America - Almonte, Maribel (2015)
More than 100 types of human papilloma virus (HPV) have been characterized by their mollecule and some 40 types, pertaining to the alpha genus, infect the genital and upper aerodigestive tracts. Based on biologic and epidemiologic evidence, several cancers have been identified as causally associated to HPV. In Peru 5 400 new cases were identified and 2 663 women died from uterine cervical cancer during 2002. That is, in Peru 7 women die daily due to this cause. The identification of the human papilloma virus as the main and necessary cause of cervical cancer has opened new perspectives for primary –thanks to the introduction of prophylactic vaccines against HPV- and secondary prevention –integrating HPV detection tests to the screening programs. We review the load of cancers associated to HPV in Latin America.